(untitled) (Western European Journal of Historical Events and Social Science, 2026)
This article analyzes studies on the history of the early medieval period in Uzbekistan as reflected in English-language academic research. In particular, it examines scholarly perspectives on the political, socio-economic, and cultural processes of the region as presented in English-language literature. The article also explores interpretations of political events, interstate relations, trade routes, ethnic processes, and religious-political movements that took place in Central Asia during the early medieval period, based on English-language studies. Furthermore, the scientific and methodological approaches employed in English-language historiography are analyzed, and their scholarly significance is evaluated from a historiographical perspective.